Production of nanoliposomes with piperine from black pepper (Piper nigrum) and its improved growth inhibitory activity on colorectal cancer cells - Nhat Minh, Le; Thi Minh Anh, Tran; Van Loc, Tran; Thi Kim Hue, Phung; Thi Thao, Do (Vietnam Journal of Biotechnology, 2021)
Black pepper (Piper nigrum) is an autoicous and decorous vine cultivated in many local regions of Gia Lai. Black pepper is one of the most commonly consumed spices, and its pungency is due to the presence of alkaloids, such as piperine. This compound represents diverse biological activities, including anti-inflammatory, anticancer, antiviral, anti-larvicidal, pesticide, anti-alzheimer’s activities, etc. However, due to its poor solubility as well as its toxic effects at high use concentration, piperine is still in limit of pharmaceutical applications. In this study, we have used black pepper seed collected at Chu Se - Gia Lai to extract piperine. The compound extracted efficiency was approximately 18% with 96.7% of purity. Based on the obtained pure piperine, the hybrid nanopiperine-CD133 monoclonal antibody (mAb^CD133) complexes were fabricated with the nanoparticle size of about 170 nm, the polydispersity index (PDI) of 0.23 and the zeta potential of -9.4 mV. The nanocomplex was subjected for growth inhibitory activities against cancer colorectal cells (HT-29 cell line). The results showed that the nanopiperine-mAb^CD133 complex exhibited significant in vitro growth inhibition HT-29 colorectal cancer cells (46.56 ± 2.78%), while the viability of healthy cells remained unaffected (17.77 ± 0.82 %). The nanocomplex could also label 12.17% of HT-29 cells, which was rather higher than 3.83% from mAb^CD133 conjugated phycoerythrin (PE) as positive control. The fabricated nanopiperine-mAb^CD133 complex has proved the enhanced cytotoxic activities against colorectal cancerous cells as well as promising biopharmaceutical potency.